The Relationship Between Parental Satisfaction and Parental Loyalty in Kindergartens: The Mediating Role of Parental Trust and Parental Relationship Commitment - Huang, Jian-Hao; Chen, Ling-Ge; Ma, Yan-Xia; Gao, Sun-Yu (Frontiers in Psychology, 2022)
This study aimed to explore the psychological mechanisms behind the relationship between kindergarten parental satisfaction and parental loyalty. This study used the parental satisfaction scale, parental trust scale, parental relationship commitment scale and parental loyalty scale on 923 kindergarten parents. The test was conducted on 923 kindergarten parents. The results of this study showed that parental satisfaction significantly and positively affected parental loyalty. Parental trust was partially mediated between parental satisfaction and parental loyalty. Parental relationship commitment was also partially mediated between parental satisfaction and parental loyalty. Regarding to parental satisfaction and parental loyalty, parental trust and parental relationship commitment had chain mediation effect between parental satisfaction and parental loyalty. The findings of this study provided valuable insights into the effect of parental satisfaction on parental loyalty and offer concrete practical suggestions for kindergarten operators to improve the loyalty of kindergarten parents.